The Relationship among Predisposing, Enabling, Reinforcing Factors and the Use of Personal Protective Equipment (PPE) in Rice Mill Workers - Demetrius Y. Y. K. Meka; Agus Setyobudi; Amelya Betsalonia Sir (Universitas Nusa Cendana, 2020)
Workers in the rice milling division have risks to work health, including experiencing lung and respiratory diseases. Every time they work, workers do not use personal protective equipment such as masks, glasses and gloves, as a result the workers feel shortness of breath, cough and taste. itching of the nose and eyes. Many factors cause workers to not use personal protective equipment, one of which is the behavior of each worker. This study aims to determine the relationship between predisposing, enabling, and reinforcing factors with the use of personal protective equipment (PPE) on rice mill workers in Central Kupang District in 2019. This study used an analytical survey method with a cross sectional study approach. The sample in this study were 40 workers spread across 10 rice mills, Central Kupang District. The data analysis used was univariate analysis and bivariate analysis with the chi square statistical test. The results of this study indicate that the factors associated with the use of personal protective equipment are the level of knowledge (p-value = 0.046) while the unrelated factors are attitude (p-value = 1,000), comfort (p-value = 1,000) and the role of co-workers. (p-value = 0.196). Suggestions for all rice mills should provide complete personal protective equipment in the workplace as well as for workers to increase knowledge by seeking information regarding the behavior of using personal protective equipment using various media so that work accidents can be prevented.